2020
DOI: 10.1101/2020.09.05.283747
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Real Time and Delayed Effects of Subcortical Low Intensity Focused Ultrasound

Abstract: Deep brain nuclei are integral components of large-scale circuits mediating important cognitive and sensorimotor functions. However, because they fall outside the domain of conventional non-invasive neuromodulatory techniques, their study has been primarily based on neuropsychological models, limiting the ability to fully characterize their role and to develop interventions in cases where they are damaged. To address this gap, we used the emerging technology of non-invasive low-intensity focused ultrasound (LI… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 72 publications
(135 reference statements)
0
8
1
Order By: Relevance
“…Beyond the above discussed changes in self-inhibition, we did not identify any differences in the region-to-region connections of the DMN in PDOC. This is in contrast with previous studies reporting differences in functional connectivity between PDOC and healthy controls, many of which consistently reported disconnections between midline DMN regions [2,54,60,61]. These typically correlate with level of consciousness (based on CRS-R score) and outcome [62].…”
Section: Dmn To Dmncontrasting
confidence: 99%
See 1 more Smart Citation
“…Beyond the above discussed changes in self-inhibition, we did not identify any differences in the region-to-region connections of the DMN in PDOC. This is in contrast with previous studies reporting differences in functional connectivity between PDOC and healthy controls, many of which consistently reported disconnections between midline DMN regions [2,54,60,61]. These typically correlate with level of consciousness (based on CRS-R score) and outcome [62].…”
Section: Dmn To Dmncontrasting
confidence: 99%
“…Previous research suggests that structural differences are more prominent in the left hemisphere in PDOC [51,52], and atrophy in the left thalamus predicts functional outcome in post-traumatic brain injury survivors [53]. Furthermore, the metabolic integrity of the left hemisphere better predicts clinical diagnosis (vegetative versus minimally conscious state) [54]. In a recent ultrasound stimulation study in 3 chronic PDOC patients, stimulation of the left thalamus elicited some promising improvements in CRS-R scores [55].…”
Section: Dmn To Dmnmentioning
confidence: 99%
“…In the present study, low-intensity transcranial ultrasound stimulation (TUS) was used to perform interventions in the human basal ganglia. TUS can noninvasively stimulate the deep brain structures with high spatial accuracy of a few millimeters (Cain et al, 2021;Darmani et al, 2022;Folloni et al, 2019;Fomenko et al, 2018;Fouragnan et al, 2019;Kubanek et al, 2020;Legon et al, 2014;Pasquinelli et al, 2019). Previous studies have reported that TUS can induce short-or long-term suppression/enhancement of the activity depending on stimulation protocols (Fomenko et al, 2020;Legon et al, 2018;Verhagen et al, 2019;Zeng et al, 2022;Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…While the exact focality of LIFU depends on several factors including the technology, specific settings, depth of the chosen focus, and the skull properties, when aiming at deep brain structures the area of maximal stimulation is approximately 0.5 cm radially by approximately 1.25 cm longitudinally. 61 Focused ultrasound can exert bioactivity through multiple mechanisms including thermogenic effects, cavitation, and mechanical agitationthe first two are typical of nonreversible, ablative, highintensity focused ultrasound (HIFU), a technique typically used for noninvasive surgery. 62 At the intensities typical of LIFU, reversible and nondamaging mechanical agitation appears to be the primary mechanism for bioactivity.…”
Section: Other Techniques (Lifu F-swt Nlt)mentioning
confidence: 99%